Mathematical Analysis of the Reliability of Modern Trolleybuses and Electric Buses; Mathematics; Vol. 11, iss. 15 - Malozemov B. V. Boris Vitaljevich; Martyushev N. V. Nikita Vladimirovich; Konyukhov V. Yu. Vladimir Yurjevich; Oparina T. A. Tatiana; Zagorodnii N. A. Nikolay; Efremenkov (Ephremenkov) E. A. Egor Alekseevich (2023, 2023)
Title screen